KEANEKARAGAMAN FAUNA TANAH DI TAMAN NASIONAL BROMO TENGGER SEMERU SEBAGAI BIOINDIKATOR TANAH BERSULFUR TINGGI - Dwi Suheriyanto (SAINSTIS, 2012)
The using of bioindikator lately become more important with the main function is to describe the existence of relevancy with biotic factor condition and abiotic area. Land fauna is enough as land indicator because it has sensitive respond to land and climate management practice, having good correlation to the land characteristic that benefits and the ecology function can describe causal chain that connects land management decision to the last productivity and plant and animal health. This research has purpose to identify kind of land fauna found in Bromo Tengger Semeru national park, analyse kinds of land fauna and analyse land fauna that can be used as land bioindikator with high sulphur standard. The   research   uses   exploration   method,   that   arrange   land   fauna observation Bromo Tengger Semeru national park and taking land sample to be analyzed in laboratory. Taking sample location in Bromo, Jemplang area (near Bromo mountain). In each location is being observed to land fauna with plot 1 X 1 m, as many as 10 plots. Land fauna found in each plots is noted about genre and amount. The sample of the land is taken, then brought to the laboratory and analyzed to find out the content of pH land, S land, organic material and C/N land. The result of this research shows that land fauna found in Bromo Tengger Semeru national park are 10 ordo, contained 29 family. Land fauna diversity in Bromo mountain is in lower area if it is compared with other area, with index 2.07 variety. Jemplang area has index variety 2.35 and Penanjakan area has index the highest fauna diversity, that is 2.73. Bromo mountain area has total sulphur  74,683  mg/1000g  land  and  it  is  the  area of  research within  highest sulphur. Land fauna used as land bioindicator within highest sulphur is ordo Brachyderinae   for   indicator   the   existence   fauna   and   Mesoveliidae   for bioindicator the inexistence of fauna.